TASPO Member to Join Band in England - Unknown (Port-of-Spain Gazette)
Sonny Roach, member of Trinidad All Steel Percussion Orchestra, who had been left in Martinique to undergo an operation, was successfully operated on and will join the other members of the band in England. The "Operation Britain Committee" received a letter from Beryl McBurnie with this information and preparations were being made to obtain a passage for Roach.
Keywords: Musicians -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago